Optimizing Electro-oxidation, Electrocoagulation and Electro-Fenton processes for Treating Model Pesticide Wastewater containing Bromuconazole - Yusuf Yavuz; Mohammed Azeez OTHMAN (Zanco Journal of Pure and Applied Sciences, 2021)
In this work the removal efficiency of Bromuconazole and chemical oxygen demand (COD) from aqueous solution using different electrochemical processes (electro-oxidation process (EOP), electrocoagulation process (ECP) and electro- Fenton process (EFP) were investigated. All experiments were achieved at the natural pH of solution. The effects of some parameters such as current density and H2O2 concentration on COD and pesticide removal efficiency have been carried out at an initial pH of ˷8.45, current density 5,10,15,20 mA/cm2, an initial pesticide concentration of 300 mg/L, 5mM Na2SO4 support electrolyte and temperature of 30oC. The COD decrease at the end of 80 minutes of treatment from ˷1200 to 167.52 mg/L by EOP, to 248.26 mg/L by ECP, and to 237.94 mg/L by EFP. Results showed that a high COD reduction was obtained by EOP (85.59%), followed by EFP (80.48%) and electrocoagulation at (79.51 %) with a constant current density of 20, 20, 15 mA/cm2 respectively. The removal of bromuconazole pesticide exhibited a pseudo-second-order reaction with rate constant 0.0009 mg-1Lmin-1. Moreover, energy consumption, the cost of degradation and sludge formation were also determined.